2015
DOI: 10.1038/emm.2014.93
|View full text |Cite
|
Sign up to set email alerts
|

Genomic assays for Epstein–Barr virus-positive gastric adenocarcinoma

Abstract: A small set of gastric adenocarcinomas (9%) harbor Epstein–Barr virus (EBV) DNA within malignant cells, and the virus is not an innocent bystander but rather is intimately linked to pathogenesis and tumor maintenance. Evidence comes from unique genomic features of host DNA, mRNA, microRNA and CpG methylation profiles as revealed by recent comprehensive genomic analysis by The Cancer Genome Atlas Network. Their data show that gastric cancer is not one disease but rather comprises four major classes: EBV-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 118 publications
5
44
0
5
Order By: Relevance
“…EBV gastric cancers having a more extensive pattern of methylation of promoter and non-promoter CpG islands. 22 In fact, EBV gastric cancers are almost exclusive of the microsatellite-instable phenotype. 6,[23][24][25] A series of characteristics are important to underscore; EBV gastric cancers lack RHOA mutations; 6,23,24 however, a decreased expression of RHOA (and CDH1) may be seen secondary to hypermethylation of the gene or its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…EBV gastric cancers having a more extensive pattern of methylation of promoter and non-promoter CpG islands. 22 In fact, EBV gastric cancers are almost exclusive of the microsatellite-instable phenotype. 6,[23][24][25] A series of characteristics are important to underscore; EBV gastric cancers lack RHOA mutations; 6,23,24 however, a decreased expression of RHOA (and CDH1) may be seen secondary to hypermethylation of the gene or its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic tests such as the GastroGenus Gastric Cancer Classifier analyse formalin-fixed cancer tissue and may be more clinically relevant [23]. Next generation sequencing can identify EBV-positive gastric tumours by quantifying viral sequences in genomic data [24].…”
Section: Gastro-oesophageal Cancermentioning
confidence: 99%
“…14 Prior studies of lymphoma malignancies suggested EBV-associated upregulation of PD-L1 on the cell surface, which is IFNg-mediated, and thus inhibits killing of infected cells by cytotoxic T cells expressing PD-1. 15 Therefore, we hypothesis that the function of EBV-specific CTLs may be affected by the acquired immune resistance indicated by the upregulation of PD-1 on CTLs and we assumed that blocking the interaction between PD-1 and PD-L1/L2 could augment the antitumor immune responses in EBVaGC.…”
Section: Introductionmentioning
confidence: 99%